"Time's Up": The Experience of Entering Residential Aged Care for Young People with Acquired Neurological Disorders and Their Families. Issue 1 (13th September 2018) - Barry, Sandra; Knox, Lucy; Douglas, Jacinta M.
Abstract : Background and aims: Previous research has highlighted that living in residential aged care (RAC) is associated with a range of negative outcomes for adults with acquired neurological disorders. This study sought to understand the lived experience of entering RAC for young people and their family members and characterise their needs during this process. Method: Data included 64 written and verbal submissions to the 2015 Senate Inquiry into the Adequacy of existing residential care arrangements available for young people with severe physical, mental or intellectual disabilities in Australia . In line with hermeneutic tradition, text was analysed using thematic analysis. Results: Entry to RAC was experienced as a complex process that coalesced around three key events: an unexpected health crisis, a directive that time's up and the individual is required to leave the healthcare setting, with a subsequent decision to move into RAC. This decision was made in the absence of time, knowledge of options or adequate support. Conclusions: Findings suggest that there are both immediate practice changes and longer term policy responses that can support the health and disability systems to uphold the rights of people with acquired disability to choose where and how they will live their lives.